Effects to perfluorooctane sulfonate (PFOS) on the mollusk Unio ravoisieri under laboratory exposure. Issue 4 (21st April 2018) - Amraoui, Imen; Khalloufi, Noureddine; Touaylia, Samir
ABSTRACT: To understand acute toxicity and oxidative stress of perfluorinated compounds in the freshwater ecosystems, we exposed freshwater mussels ( Unio ravoisieri ) to perfluorooctane sulfonate (PFOS), over a range of concentrations from 10 to 100 mg/L, in a laboratory experiment. Lethal concentration (LC50) was of about 65.9 mg/L after 96 h of exposure. The oxidative stress was assessed in gill and digestive gland of the freshwater mussels after 7 days of exposure to different nominal PFOS concentrations (C1= 2 mg/L, C2 = 6 mg/L and C3= 10 mg/L). C1 and C2 increased significantly ( p  < .05) the superoxide dismutase activity in both tissues compared, while the highest C3 decreased the enzyme activity. This implements an unfavourable response that highlights the excess of reactive oxygen species produced after contamination. The Catalase activity was also increased by about 40.05% and 66.63%, respectively, in gill and digestive gland after exposure to C3. The Malondialdehyde (MDA) level was increased in both gill and digestive gland in a concentration-dependent pattern. In contrast, the contamination of U. ravoisieri by PFOS did not affect the acetylcholinesterase activity in both organs ( p  > .005). These results provided information on potential biomarkers that could be effectively applied for the monitoring of freshwater ecosystem using indicator species such as U. ravoisieri .